2018
DOI: 10.1016/j.apsoil.2017.11.022
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effects of prolonged freshwater and saline flooding on nitrogen cycling in an agricultural soil

Abstract: Due to climate change, the frequency and duration of flood events are predicted to increase in many regions of the world. This is expected to cause large changes in soil functioning and to a progressive decline in soil quality such as reduced rates of nutrient cycling, enhanced greenhouse gas emissions and loss of soil biodiversity. There is a knowledge gap, however, on how temperate agricultural soils under different management practices (e.g. manure application) respond to prolonged river or coastal flooding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 67 publications
1
10
0
Order By: Relevance
“…Research done by Sánchez-Rodríguez et al [119] have the same results with Bossio and Scow [120] and Bai et al [116] where Gram-negative bacteria decreased under flooding with fresh water and Gram-positive bacteria increased. Studies done by Bal and Adhya [48] shows that inoculation of seeds with Gram-positive plant growth promoting rhizobacteria (Bacillus sp., Microbacterium sp., Methylophaga sp., and Paenibacillus sp.)…”
Section: Submergencesupporting
confidence: 68%
See 1 more Smart Citation
“…Research done by Sánchez-Rodríguez et al [119] have the same results with Bossio and Scow [120] and Bai et al [116] where Gram-negative bacteria decreased under flooding with fresh water and Gram-positive bacteria increased. Studies done by Bal and Adhya [48] shows that inoculation of seeds with Gram-positive plant growth promoting rhizobacteria (Bacillus sp., Microbacterium sp., Methylophaga sp., and Paenibacillus sp.)…”
Section: Submergencesupporting
confidence: 68%
“…helps rice variety IR42 to withstand submergence stress by reducing the inhibitory effect of ethylene stress. Although Unger et al [76] stated that flooding reduced fungal communities, Sánchez-Rodríguez et al [119] reported that AMF density was increased in the event of flood in saline water. Several studies showed that density of AMF community increased with low precipitation which reduced soil humidity and elevated O 2 concentration [68].…”
Section: Submergencementioning
confidence: 99%
“…Depending on the typology of the flood event, i.e. duration, depth, origin of the water (Sánchez-Rodríguez et al, 2018), and the soil/vegetation combination, prolonged inundation is expected to impact upon soil functions to different extents. Bünemann et al (2018) has recently reviewed the multiple aspects and definitions of soil quality.…”
Section: Introductionmentioning
confidence: 99%
“…Each of these sectors requires a certain need for water, which today depends largely on the level of development of infrastructure and logistics, elements closely related to the degree of urbanization and alignment to specific standards. A frequently analyzed aspect is the quality of surface water [9][10][11][12], including the peak or minimum flow periods. The demand for water remains constant or increasing, regardless of periods of drought.…”
Section: Introductionmentioning
confidence: 99%